The Economy Wide Impact of Investment on Infrastructure for Electricity in Ethiopia: A Recursive Dynamic Computable General Equilibrium Approach - Borojo, Dinkneh Gebre (International Journal of Energy Economics and Policy, 2015)
This study has applied a recursive dynamic CGE model to examine the economic impact of investment on infrastructure for electricity using an updated 2009/10 Social Accounting Matrix. Three simulations (foreign saving, domestic household and enterprises saving and mix of foreign and domestic saving to finance the investment) in combination with TFP of industrial and service sectors are used. The findings of the study have shown the improvement of the real GDP, output of industrial and service sectors in all simulations. Nonetheless, mixed effects have found on household consumption and trade balance. The highest growth of real GDP is registered when the investment on electricity is fully financed by domestic household and enterprise saving. However, household consumption expenditure has grown at negative rate worsening the welfare of households. Investment on electricity fully financed by foreign saving is resulted in lower growth rate of real GDP due to worsening of net export. In addition, it has benefits for households as it increases their welfare. But it is to be repaid in the future that would increase indebtedness of the country. So, financing the investment partly by domestic household saving and foreign saving would be worthwhile. Keywords: Electricity Infrastructure, Economy, Recursive Dynamic CGE Model JEL Classifications: C6; Q4; Q43